Hibridismo cultural y literatura en el contexto de una “poética de la relación” - Rosales Rodríguez, Amán (Studia Romanica Posnaniensia, 2013)
Adopting as main conceptual framework the proposals of the important thinker and poet from Martinica, Édouard Glissant (1928-2011), about a “poetics of relation”, the article considers the way in which a significant part of the contemporary Spanish speaking literary creation — precisely in virtue of its hybrid or mixed cultural nature — is a good example of the fertility of Glissant’s “poetics of relation” — in which other key concepts of Glissant’s theoretical point of view, like the “archipelagic thought” and the “Whole-World”, are included. Thus, the convergence between certain theoretical perspectives rooted in the francophone Caribbean context and similar intuitions literary developed in the Hispanic American region is highlighted.